Water use strategy determines the effectiveness of internal water storage for trees growing in biofilters subject to repeated droughts - Hanley, Paul A.; Livesley, Stephen J.; Fletcher, Tim D.; Szota, Christopher (The Science of the total environment, 2023)
Impervious surfaces create large volumes of stormwater which degrades receiving waterways. Incorporating trees into biofilters can increase evapotranspiration and therefore reduce stormwater runoff. Tree species with i) high water use, ii) drought tolerance and iii) rapid and full recovery after drought have been suggested for biofilters to maximise runoff reduction while minimising drought stress. Moisture availability fluctuates greatly in biofilter substrates and trees growing in biofilters will likely experience multiple, extended drought events that increase trade-offs between these traits. Providing an internal water storage has the potential to reduce tree drought stress and increase evapotranspiration. Two urban tree species (Agonis flexuosa and Callistemon viminalis) were grown in plastic drums with biofilter profiles. Three irrigation treatments were used: well-watered, drought with an internal water storage and drought without an internal water storage. Transpiration, leaf water potential and biomass were measured to determine the effect of biofilter internal water storage and repeated drought events on tree water use, drought stress and growth. Biofilter internal water storage improved water use and reduced drought stress for A. flexuosa, whereas C. viminalis reduced leaf loss but saw no change in water use or drought stress. A. flexuosa with biofilter internal water storage was able to recover transpiration to well-watered levels after repeated droughts, while C. viminalis experienced reduced recovery ability. It is recommended all biofilters planted with trees should have internal water storage. In systems with lower moisture availability a species with more stomatal control, such as A. flexuosa, is recommended. If selecting a species with less stomatal control, such as C. viminalis, the internal water storage volume needs to be increased to avoid drought stress. [Display omitted] •Trees in biofilters with and without internal water storage were repeatedtly drought stressed.•Trees with more stomatal control with storage improved water use and recovery.•Trees with less stomatal control with storage improved leaf retention.•Storage volumes need to be coordinated with water use to reduce trade-offs.